The role of urodynamic study in the diagnostic of urinary incontinence in women - Zydek, Cezary; Łowicki, Roman (Menopause Review/Przegląd Menopauzalny, 2004)
Urinary incontinence (UI) in women is a common problem, which physicians of different specialities cope with. The differential diagnosis of certain types of UI causes a lot of difficulties. In this paper we would like to present the evaluation of urodynamic investigation in diagnosis of UI in women. We have retrospectively analized 130 cases of paients that were submitted to urodynamic study at our clinic between january 2003 and march 2004. The diagnosis of UI was set up at the basis of history taking, urine voiding diary, physical examination (including gynecological, urological and neurological examination in case of suspicion of neurogenic basis) and urodynamic investigation. The urodynamic test was carried out using Mercur 4000, WIEST. Among this group results of our investigation were: 73.8% of patients had SUI, 5.7% UUI and 20.5% MUI. We have also indicated signifficant differencies of measured parameters between women with SUI and UUI. The urinary bladder of women suffering from UUI showed overreactivity and the values (in ml) of void first sensation, void strong desire and maximal cystometric capacity were significantly lower then among women with SUI. The values of detrusor pressure during top bladder filling were the lowest in case of SUI and the highest in UUI. Differencies concerned also uroflowmetry data, where decreasing of the voided volume and maximal flow rate by women with UUI were settled. Our investigation prooved that urodynamic testing is the most objective form of lower urinary tract diagnostics. It also allows to settle preciselly the form of urinary incontinence and its grade. This testing should always be taken in case of nonsurgical treatment failure and before planned surgical treatment.